The First Horsemen - Frank Trippett (USA Time life Books, 1974)
The Emergence of Man . Examines the beginnings of the relationship between men and horses and describes the way of life of the Scythians and other ancient mounted nomads of Eurasia . Frank Trippett and the editors of Time-Life Books
Keywords: History, Geography and Archaeology (3GdJGQjN hGdLZQGajG hGdBKGQs; Ethnology -- Asia; Horsemen and horsewomen -- History; Scythians; Nomads